2006
DOI: 10.1249/01.mss.0000189317.08635.1b
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Muscle Patterns and Spine Load during Various Forms of the Push-Up

Abstract: These data will help guide exercise selection for individuals with differing training objectives and injury history.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
86
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(102 citation statements)
references
References 10 publications
5
86
0
1
Order By: Relevance
“…These findings are in accordance with authors who reported greater TRICEP activation with push-ups on a Swiss ball (Lehman et al, 2006) than on the floor. On the other hand, Freeman et al (2006) found no differences between conditions, although the unstable device used in this study consisted of two basketballs that probably lacked the appropriate degree of instability to lead to changes in muscle activation.…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…These findings are in accordance with authors who reported greater TRICEP activation with push-ups on a Swiss ball (Lehman et al, 2006) than on the floor. On the other hand, Freeman et al (2006) found no differences between conditions, although the unstable device used in this study consisted of two basketballs that probably lacked the appropriate degree of instability to lead to changes in muscle activation.…”
Section: Discussionmentioning
confidence: 53%
“…Other studies reported similar DELT activation during push-ups with the hands on two separate balls (Freeman et al, 2006) in comparison with a stable surface. Despite variations in gleno-humeral joint position during the exercise and different instability degrees may change muscle activity results.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations